Peran Guru Pendidikan Agama Buddha dan Budi Pekerti dalam Meningkatkan Karakter Peserta Didik di Kelas IIA SD Metta Maitreya Pekanbaru - Sutikno, Yadi; Chowmas, Dharmaji; Suryati, Suryati; Sepriyadi, Hendri; Lily, Lily (STAB Maitreyawira, 2026)
Based on initial interviews and formative tests which showed that the character of discipline and perseverance of three students of class IIA Metta Maitreya Elementary School Pekanbaru was still lacking. Based on this problem, there needs to be a study on the Role of Buddhist Religious Education and Character Education Teachers in Improving the Character of Students in Class IIA Metta Maitreya Elementary School Pekanbaru as a solution for the three students. The research method used is a qualitative method. The time of this research started from January to March 2026. The research location is Metta Maitreya Elementary School Pekanbaru which is located on Jalan Tuanku Tambusai, Puri Nangka Sari Complex, Pekanbaru. The data source came from the Buddhist education and Character Education teachers of class IIA Metta Maitreya Elementary School Pekanbaru. Data collection techniques through observation, interviews, and documentation. The conclusion of this study is that Buddhist education and Character Education teachers play a role in improving the character of discipline and perseverance of class IIA students of Metta Maitreya Elementary School Pekanbaru.